Comparative analysis of chloroplast genome and new insights into phylogenetic relationships of Ajuga and common adulterants - Shang, Mingyue; Wang, Jiale; Dai, Guona; Zheng, Jiamei; Liao, Binbin; Wang, Jing; Duan, Baozhong (Frontiers in Plant Science, 2023)
The potential contamination of herbal medicinal products poses a significant concern for consumer health. Given the limited availability of genetic information concerning Ajuga species, it becomes imperative to incorporate supplementary molecular markers to enhance and ensure accurate species identification. Here, the chloroplast (cp) genomes of seven species were characterized, exhibiting lengths ranging from 150,342 bp to 150,472 bp, encompassing 86 -88 protein-coding genes (PCGs), 35 -37 transfer RNA, and eight ribosomal RNA. The repetitive sequences, codon uses, and cp genomes of seven species were highly conserved, and PCGs were the reliable molecular markers for investigating the phylogenetic relationship within the Ajuga genus. Moreover, four mutation hotspot regions (accD-psaI, atpH-atpI, ndhC-trnV(UAC), and ndhF-rpl23) were identified within cp genomes of Ajuga, which could help distinguish A. bracteosa and its contaminants. Based on cp genomes and PCGs, the phylogenetic tree preliminary confirmed the position of Ajuga within the Lamiaceae family. It strongly supported a sister relationship between Subsect. Genevense and Subsect. Biflorae, suggesting the merger of Subsect. Biflorae and Subsect. Genevenses into one group rather than maintaining separate categorizations. Additionally, molecular clock analysis estimated the divergence time of Ajuga to be around 7.78 million years ago. The species authentication, phylogeny, and evolution analyses of the Ajuga species may benefit from the above findings.